Career crescendo: An experimental analysis of a 6-week work-site intervention to determine the developmental capacity of psychological capital. Issue 9 (6th November 2019) - Sharp, Ryan
Abstract : Purpose: Research surrounding psychological capital (PsyCap) continues to expand as scholars and organizational leaders look to the strengths of positive organizational behavior (POB) and its effects in the workplace. Although previous research underscores connections between PsyCap and various organizational outcomes, there remains little research on its actual development. The purpose of this paper is to determine the efficacy of a six-week work-site intervention in improving PsyCap. The study included 49 individuals ( n =32 assigned to the treatment group and n =17 to the comparison group). Using a pretest/posttest experimental design, the study showed that the intervention was efficacious in helping employees to develop greater PsyCap. Design/methodology/approach: This study was part of a larger mixed methods design aimed at determining the efficacy of a work-site intervention in improving the PsyCap of employees. This design was chosen because it maximizes the strengths of both qualitative and quantitative methods while minimizing each of their weaknesses (Creswell and Plano Clark, 2007;Tashakkori and Teddlie, 1998 ). The specific mixed methods design implemented was the explanatory design using the participant selection model. This is a two-phase, sequential approach which began with a quantitative analysis and then drew upon those data to determine individuals who will be asked to participate in a follow-up study. Findings: The purpose of this study was to determine the impact of a work-site intervention on the participants' PsyCap in determining its developmental capacity. Previous studies have demonstrated strong correlations between PsyCap and many of the positive outcomes managers and supervisors desire for their employees –high productivity, low absenteeism, positive organizational citizenship, etc. (Luthans et al., 2013 ; Youseff and Luthans, 2007). With the results of the present study showing significantly greater improvement for the treatment group than their counterparts in the comparison group, it demonstrates that PsyCap can be developed and, consequently, these positive outcomes can accessed by a focused work-site intervention. Originality/value: This paper builds on work already being done but focuses on the following significant gap in the literature: Can PsyCap be developed using work-site interventions? This study provides a compelling answer to that question and thus pushes the study of POB forward in its development.